Postural control responses to different acute and chronic training load profiles in professional rugby union - Troester, J. C.; Duffield, R. (The Journal of Strength and Conditioning Research, 2022)
The current investigation identified the response of postural control (PC) measures of single-leg balance and landing to different accumulated training load profiles representing normal, higher, and spiked loads. Twenty-two professional rugby union players performed single-leg balance and landing tests on a 1,000-Hz force plate on the first training day of 24 weeks across the season after 36 hours of recovery. Internal (session rating of perceived exertion training load) and external (total and high-speed running distance) load measures were monitored during all training sessions and matches. Calculations of acute (7-day rolling average), chronic (28-day rolling average), and acute-to-chronic workload ratio were determined. Three-week load profiles were identified that represented normal, spike, and higher load profiles to determine the effect on PC, which were analyzed using 2-way repeated-measures analysis of variance. A significant effect of load profile on landing impulse on the dominant (p = 0.005) and nondominant legs (p = 0.001) was identified, with significantly greater impulse measures in the spike and higher load profiles (p = 0.001-0.041) compared with the normal load profile. Significant load profile × week interactions (p < 0.05) were identified for landing peak force on the dominant leg and impulse on both legs suggesting a decrement during the spike load profile and increased impulse in the higher load profile. No effects (p > 0.05) were identified for load profile changes in single-leg balance sway velocity or single-leg landing time to stabilization. The respective landing responses may indicate altered movement strategies under spike and higher load profiles resulting from neuromuscular fatigue in response to the accumulated load.